Impairments in Deductive Reasoning and Working Memory in Parkinson’s Disease - Shelley Channon (Behavioural Neurology)
This study was designed to investigate the nature and extent of executive impairments in medicated subjects with Parkinson's disease (PD) and matched control subjects. They performed two tasks involving strategic processing, deductive reasoning and memory updating. PD patients differed significantly from controls in solving two- and four-dimensional deductive reasoning problems, and they also showed impairment in memory updating. The findings are discussed in relation to previous studies which have shown deficits in strategic processing in PD.